RESEARCH-BASED TRAINING: EUROPEAN APPROACHES TO ITS CHARACTERISTICS - Pavliuk, Roman O. (Educological discourse, 2017)
The article analyzes the characteristics of European approaches to the definition of the system of research-based training. Based on theoretical and empirical research of leading European and world scientists it was defined the concept of research-based training, its key features and characteristics. It is presented features of interaction of teacher and student in education system of research-based training, described the main types of tasks that can be effective in the formation of a new generation of specialists, researchers who are gaining higher education. The basic approaches to designing of the system of research-based training are suggested and presented the main differences between the system of «traditional» education and the system of research-based training.